ORGANIZING ACCOUNTING POLICIES IN TRADE ENTERPRISES - Ziyadullayevna, Bobomuradova Sarvinoz (International Journal of Accounting Innovation, 2025)
Objective: This article analyzes the organization of accounting policies in trade enterprises based on the legislation of the Republic of Uzbekistan. Properly structured accounting policies ensure financial stability and compliance with legal requirements. Method: The study examines legislative requirements, international experiences, and practical challenges in implementing accounting policies in trade enterprises. Data analysis is conducted using tables and graphs to illustrate key findings. Results: The analysis reveals gaps in the current legislative framework and identifies challenges faced by trade enterprises in organizing their accounting policies. The study highlights discrepancies between regulatory requirements and practical implementation. Novelty: This study provides a comprehensive evaluation of Uzbekistan's accounting policies in trade enterprises by comparing them with international standards. It offers insights into improving financial stability and regulatory compliance through effective policy implementation.